1961
DOI: 10.1071/ph610497
|View full text |Cite
|
Sign up to set email alerts
|

A Catalogue of Radio Sources Between Declinations ?50° and ?80°

Abstract: SummaryA catalogue has been prepared of the radio sources observed between declinations -50° and -80°, using the Sydney cross-type radio telescope at a wavelength of 3·5 m; a total of 219 sources is listed. This supplements the earlier catalogues for the declination ranges +10° to -20° and -20° to -50°. In addition to the positions and intensities of the sources, angular sizes of 42 of the strongest sources are given. As before, identifications with bright optical objects have been sought, and a number of poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

1973
1973
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 4 publications
2
46
0
Order By: Relevance
“…With its first detection at radio wavelengths, the SNR MSH 15-56 (G326.3−1.8) became the prototype for the composite class of SNRs (Mills et al 1961;Milne et al 1979). A lower limit on its distance of 3.1 kpc has been established by the H i absorption profile of Goss et al (1972), while Rosado et al (1996) found a distance of 4.1 kpc through Hα velocity measurements, the distance we adopt in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…With its first detection at radio wavelengths, the SNR MSH 15-56 (G326.3−1.8) became the prototype for the composite class of SNRs (Mills et al 1961;Milne et al 1979). A lower limit on its distance of 3.1 kpc has been established by the H i absorption profile of Goss et al (1972), while Rosado et al (1996) found a distance of 4.1 kpc through Hα velocity measurements, the distance we adopt in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…MSH 15−52 (G320.4−1.2) is a complex supernova remnant (SNR) that was discovered in radio wavelengths by Mills et al (1961). Its radio appearance is dominated by two spots, a brighter one to the northwest and a fainter one to the southeast.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous radio observations of A3667 (e.g. Mills, Slee & Hill 1961;Ekers 1969;Schilizzi 1975;Goss et al 1982;Rottgering et al 1997) have noted the bright extended structures in A3667 but failed to image the entire extent of both relics. The first study of the entire region at high resolution (∼ 6 arcsec), including both the NW and SE relics, was carried out by Johnston-Hollitt (2003) at 1.4 GHz.…”
mentioning
confidence: 99%
“…The presence of a faint radio halo in the centre of the cluster has also been reported (Johnston-Hollitt 2004;Carretti et al 2013). The only study of A3667 below 300 MHz was performed more than five decades ago by Mills et al (1961) at 86 MHz using the Mills Cross Telescope with a resolution of 50 arcmin. The large angular extent and high surface brightness of the relics and the detection of a faint radio halo and bridge (at frequencies of 1.4-3.3 GHz) in A3667 make it an excellent laboratory in which to carry out low-frequency observations to study the ICM.…”
mentioning
confidence: 99%